2013
DOI: 10.1002/marc.201300339
|View full text |Cite
|
Sign up to set email alerts
|

Forming of Polymer Nanofibers by a Pressurised Gyration Process

Abstract: A new route consisting of simultaneous centrifugal spinning and solution blowing to form polymer nanofibers is reported. The fiber diameter (60–1000 nm) is shown to be a function of polymer concentration, rotational speed, and working pressure of the processing system. The fiber length is dependent on the rotational speed. The process can deliver 6 kg of fiber per hour and therefore offers mass production capabilities compared with other established polymer nanofiber generation methods such as electrospinning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
305
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 201 publications
(314 citation statements)
references
References 28 publications
6
305
1
2
Order By: Relevance
“…Fabrication of Fibers. The fibers were fabricated using a previously reported 49 in-house built experimental setup, using the principle of infusion gyration ( Figure 1; also see Supporting Information Video S1). The device consists of a hollow aluminum rotary vessel, 25 mm in height and 60 mm in diameter, and contains 20 small round orifices.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of Fibers. The fibers were fabricated using a previously reported 49 in-house built experimental setup, using the principle of infusion gyration ( Figure 1; also see Supporting Information Video S1). The device consists of a hollow aluminum rotary vessel, 25 mm in height and 60 mm in diameter, and contains 20 small round orifices.…”
Section: Methodsmentioning
confidence: 99%
“…The viscosity of solution can vary during gyration due to a temperature gradient occurring through the polymer jets during solvent evaporation, and this could also be facilitated by increasing rotation speed [14]. Mahalingam and Edirisinghe [14] have indicated that the time constant of shearing forces applied on polymer jets during pressurised gyration will be decreased with increasing rotation speed. In addition, the time constant of shearing forces governs the responses of polymer chains, i.e.…”
Section: Fibre Morphologymentioning
confidence: 99%
“…fibres, microbubbles, capsules etc [14,15]. It effectively utilizes high speed rotation to extrude several solution jets in parallel from orifices that are located on the vessel surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations